2019
DOI: 10.1021/acs.chemmater.9b02322
|View full text |Cite
|
Sign up to set email alerts
|

Role of Structural Defects in the Adsorption and Separation of C3 Hydrocarbons in Zr-Fumarate-MOF (MOF-801)

Abstract: An effective separation of propylene/propane mixtures is one of the most important processes in the petrochemical industry. Incidentally this separation is challenging due to the extensive similarities between both gases in terms of physicochemical properties such as, but not only limited to, boiling point, kinetic diameter and molecular weight. A drive to switch to less energy consuming processes, like adsorption or membrane separation, has highlighted several microporous metal organic frameworks as promising… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 68 publications
3
56
0
Order By: Relevance
“…Paul et al reported that MOF-801 containing defects could selectively adsorb C 3 H 8 when separating C 3 H 6 /C 3 H 8 mixtures, and at the same time increase the adsorption capacity and diffusion rate. [38] This work proves that the selectivity of MOF materials for C 3 H 6 /C 3 H 8 separation can be controlled by MOF defect chemistry, and opens up a new path for the separation of C 3 H 6 / C 3 H 8 mixtures by MOF materials.…”
Section: Adsorption and Separation For C 3 H 6 /C 3 H 8 Mixturessupporting
confidence: 54%
“…Paul et al reported that MOF-801 containing defects could selectively adsorb C 3 H 8 when separating C 3 H 6 /C 3 H 8 mixtures, and at the same time increase the adsorption capacity and diffusion rate. [38] This work proves that the selectivity of MOF materials for C 3 H 6 /C 3 H 8 separation can be controlled by MOF defect chemistry, and opens up a new path for the separation of C 3 H 6 / C 3 H 8 mixtures by MOF materials.…”
Section: Adsorption and Separation For C 3 H 6 /C 3 H 8 Mixturessupporting
confidence: 54%
“…N 2 adsorption‐desorption isotherms at 77 K (Figure 2 d and Table 1) evidenced that these materials are highly porous, with Brunauer‐Emmett‐Teller (BET) surface area of 1035(±5) m 2 g −1 (MOF‐801(Zr)), 735(±6) m 2 g −1 (MOF‐801(Hf)) and 780(±5) m 2 g −1 (MOF‐801(Ce)). These values are slightly larger than those for the pristine MOF‐801(Zr) (680 m 2 g −1 ), which suggests that these MOFs present a significant amount of defects, as reported previously using other synthesis conditions [18] . In order to determine the defect nature (missing nodes or linkers), FT‐IR analysis was carried out (see Figure S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 53%
“…The resulting structure showed defects in the structure which have been confirmed by single‐crystal XRD. [ 88 ] Afterward, many research works have reported the synthesis of defects in MOFs by using the typical technique but with different monocarboxylic modulators such as acetic acid (AA), [ 93–95 ] formic acid (FA), [ 96,97 ] difluoro acetic acid (DFA), [ 98 ] trifluoroacetic acid (TFA), [ 99 ] and others. [ 100,101 ]…”
Section: Defects In Mofsmentioning
confidence: 99%